(untitled) (Research, Society and Development, 2021)
The occupational therapist is one of the professionals who can make up the Family Health Support Centers (NASF). The general objective of this study was to investigate the contribution of occupational therapists to the NASF team in the national scientific literature. It was a bibliographic research, through an integrative descriptive review. The search strategy was performed in the Virtual Health Library (VHL), Latin American and Caribbean Literature in Health Sciences (LILACS), National Collection of SUS Information Sources (ColecionaSUS) and Brazilian Institutional Journal of Therapy databases OccupationalREVISBRATO, from September to November 2020, using the following descriptors: “primary health care”, “occupational therapy”, “family health” with the Boolean operator “AND” for the specificity of the bibliographic survey. The inclusion criteria defined for the selection were: articles published in Portuguese that portrayed the theme, published and indexed in the aforementioned databases in the last five years, excluding those that were not available in full. Fourteen papers on the role of occupational therapists at NASF were selected. It was found that therapeutic groups and workshops, home visits, the organization of community groups and meetings with teams from the Family Health Strategy (ESF) were the most recurrent forms of work of these professionals in the NASF, where they relied on matrix support and in community-based rehabilitation. It was concluded that the work of the occupational therapist in the NASF is a process of building in the fields of health promotion and disease prevention, developing an integral and interdisciplinary health practice and contributing to the emancipation of subjects in their various social roles, favoring human and community development.